Latitude drives diversification in Madagascar's endemic dry forest rodent Eliurus myoxinus (subfamily Nesomyinae). (7th August 2013) - Shi, Jeff J.; Chan, Lauren M.; Rakotomalala, Zafimahery; Heilman, Amy M.; Goodman, Steven M.; Yoder, Anne D.
<x xml:space="preserve">Abstract</x> Numerous hypotheses have been proposed for the historical processes governing the rich endemism of Madagascar's biodiversity. The 'watershed model' suggests that drier climates in the recent geological past have resulted in the contraction of forests around major watersheds, thereby defining areas of endemism. We test whether this hypothesis explains phylogeographical patterns in a dry forest‐dependent rodent, Eliurus myoxinus, an endemic species widely distributed through western Madagascar. We sequenced the mitochondrial cytochrome b locus and nuclear introns of the β‐fibrinogen and the growth hormone receptor genes for E. myoxinus. Using a parametric bootstrapping approach, we tested whether the mitochondrial gene tree data fit expectations of local differentiation given the watershed model. We additionally estimated population differentiation and historical demographic parameters, and reconstructed the spatial history of E. myoxinus to highlight spatial and temporal patterns of differentiation. The data do not support the watershed model as a clear explanation for the genetic patterns of diversity within extant E. myoxinus populations. We find striking patterns of latitudinal genetic structure within western Madagascar, and indicate possible roles for environmental and ecological gradients along this axis in generating phylogeographical diversity. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 500–517.